2020
DOI: 10.1016/j.cegh.2020.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence and associated risk factors of Toxoplasma gondii infection in a representative Australian human population: The Busselton health study

Abstract: Introduction: Despite being identified as one of the top neglected parasitic infections, Toxoplasma gondii has received little recognition in Australia with no previously published prevalence data from the general human population. The objectives of the current study were to: determine the prevalence of evidence of exposure to T. gondii infection in an Australian community dwelling population, and: identify associated risk factors. Methods: Sera from 75 males and 75 age-matched females living in Busselton, Wes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
(53 reference statements)
1
2
0
Order By: Relevance
“…For all adjusted regression models, no significant relationship was detected between T. gondii infection and asthma. These findings are consistent with two other large cross-sectional studies in Scotland and Australia that found no association between T. gondii seropositivity and asthma (14,33). While our results appear to contradict several case-control studies that have found a protective effect of T. gondii infection on allergy symptoms and asthma, these studies did not consider confounders which could impact exposure to a diversity of microorganisms and their products, such as socioeconomic status or number of siblings (34,35).…”
Section: Discussionsupporting
confidence: 92%
“…For all adjusted regression models, no significant relationship was detected between T. gondii infection and asthma. These findings are consistent with two other large cross-sectional studies in Scotland and Australia that found no association between T. gondii seropositivity and asthma (14,33). While our results appear to contradict several case-control studies that have found a protective effect of T. gondii infection on allergy symptoms and asthma, these studies did not consider confounders which could impact exposure to a diversity of microorganisms and their products, such as socioeconomic status or number of siblings (34,35).…”
Section: Discussionsupporting
confidence: 92%
“…Human are dead-end host for T. gondii with up to 80% given chronic asymptomatic disease. [ 7 8 ] Women during pregnancy and immunocompromised persons (cancer, Rheumatoid arthritis, transplant, and HIV/AIDS infected) include the high risk groups for T. gondii . [ 9 10 11 12 ]…”
Section: Introductionmentioning
confidence: 99%
“…Their study also concluded that there is no association between consumption of unwashed vegetables or fruits and seropositivity of T. gondii infection since 3.45% of the subjects who denied of consuming unwashed vegetables and fruits were found seropositive. Molan et al (2020) also did not identify any risk factor associated with the seroprevalence of T. gondii infection. It has been reported that immune status that develop in response to acute T. gondii infection and that during pregnancy are antagonistic to each other (Borges et al, 2018).…”
Section: Discussionmentioning
confidence: 79%